Exploration of Islamic Values in Controlling Muslim Consumption Behaviour in Bandung City: A Phenomenological Study of The Digital Era - Sudana, Sudana; Marlina, Lina; Awaludin, Latief (Global Review of Tourism and Social Sciences, 2025)
Aggressive digital promotions encourage excessive consumption patterns that are not based on needs. From an Islamic perspective, uncontrolled consumption can be contrary to sharia principles, but the extent to which Islamic values are able to control consumer behaviour still needs to be studied further. Therefore, this study aims to explore the role of Islamic values in controlling the consumer behaviour of Muslim consumers in Bandung City. This study uses a qualitative method with a phenomenological approach to understand the subjective experiences of Muslim consumers in dealing with social media promotions. The sample was selected through purposive sampling, involving consumers who actively shop online. Data were collected through interviews and analysed using NVivo. The results showed that Islamic values such as qana'ah, prohibition of israf, maslahah, hisbah, zuhud and tawakal play a role in controlling consumption. NVivo analysis found that the prohibition of israf, qana'ah, and maslahah were dominant factors in limiting excessive consumption. Understanding hisbah helps consumers be more selective about promotions. Meanwhile, the attitude of zuhud forms psychological resilience to consumption pressures, while tawakal instils inner peace and reduces the tendency to shop in response to financial anxiety.